Gambaran Pengetahuan pada Ibu Tentang Demam Tifoid Anak di Ruang Theresia Rumah Sakit Santa Elisabeth Medan Tahun 2024 - Yensika Dwi Putri Meha; Rusmauli Lumban Gaol; Indra Hizkia Perangin-Angin; Gryttha Tondang (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Typhoid fever is an infection of Salmonella enterica bacteria, especially Salmonella typhi which causes typhoid fever that occurs suddenly. Typhoid fever, also known as typhoid fever, is a disease with a high case rate. Parents' lack of attention to children's tendency to buy unhealthy foods will affect children's behavior in buying food and family history of having experienced typhoid fever and personal hygiene is a significant factor in increasing the risk of typhoid fever. The purpose of this study is to find out the Overview of Knowledge in Mothers About Pediatric Typhoid Fever. This type of research is descriptive design. Sampling is carried out by Accidential Sampling with a total of 30 respondents and data collection using questionnaires. The study shows that 18 respondents (60.0%) are knowledgeable about the causes of the sufficient category, 23 respondents (76.7%) are knowledgeable about the signs and symptoms of the sufficient category, 17 respondents (56.7%) are knowledgeable about prevention of the sufficient category, 23 respondents (76.7%) are knowledgeable about the treatment of the sufficient category and 21 respondents (70.0%) are knowledgeable about typhoid fever. Based on the results of the study, it is found that most of the mothers at Santa Elisabeth Hospital Medan have enough knowledge about typhoid fever. Researchers urge to pay more attention to children's hygiene, to maintain children's health and avoid diseases such as typhoid.